Electronic threats and cyber security in the Arab world (Numerus academy review, 2026)
Throughout history, the Arab region has been a region of various conflicts and threats, whether traditional or new. The framework of security issues in their dimensionsis no longer defined internally for any country, but has extended to the regional andinternational framework. And in light of the digital revolution and the accompanyingdevelopment that touched all fields and the total sweep of cyberspace, the characteristicsof security and conflict in the region changed, especially after the year 2011 and thesubsequent Arab spring revolutions, through which various new security threats,especially electronic ones, increased, thus transforming the arena of conflict from the ground to reality. Blue space.